Development of Highly Potent and Selective Steroidal Inhibitors and Degraders of CDK8 - Hatcher, John M. (ACS Med Chem Lett, 2018)
[Image: see text] Cortistatin A is a natural product isolated from the marine sponge Corticium simplex and was found to be a potent and selective inhibitor of CDK8. Many synthetic groups have reported total syntheses of Cortistatin A; however, these syntheses require between 16 and 30 steps and report between 0.012–2% overall yields, which is not amenable to large-scale production. Owing to similarities between the complex core of Cortistatin A and the simple steroid core, we initiated a campaign to design simple, more easily prepared CDK8 inhibitors based on a steroid scaffold that would be more convenient for large-scale synthesis. Herein, we report the discovery and optimization of JH-VIII-49, a potent and selective inhibitor of CDK8 with a simple steroid core that has an eight-step synthesis with a 33% overall yield, making it suitable for large-scale preparation. Using this scaffold, we then developed a bivalent small molecule degrader, JH-XI-10-02, that can recruit the E3 ligase CRL4(Cereblon) to promote the ubiquitination and proteosomal degradation of CDK8.